A Study on Power System Retrofit for Cessna-172S Aircraft by Using Hydrogen Fuel Cell and Battery Hybrid - Oguz Kagan Keles; Ibrahim Hakyemez; Mustafa Bagriyanik; Ozcan Kalenderli (IEEE Access)
The electrification of aviation is predominantly driven by environmental concerns associated with emissions. In this context, while the More Electric Aircraft and Hybrid Electric Aircraft concepts are currently at the forefront, the long-term objective is the utilization of All Electric Aircraft. Presently, the transition to All Electric Aircraft, which includes the electrified propulsion system, seems challenging due to the significant energy and power demands of aircrafts, given that the specific energy of recent energy storage technologies and power density of other electrical parts are not at the desired levels. Nevertheless, various scientific findings are being explored to accelerate this process and fuel cells are emerging as a solution. This study examines the retrofitting of a Cessna 172S, selected as the baseline aircraft, into a fully electric version with a hybrid configuration combining a battery and fuel cell. The modification process includes the development of an electrical power system architecture, selection of the required components, and modeling of the system elements. The new configuration of the platform is investigated through various simulations to evaluate the impacts on power sharing of the battery and fuel cell, and a comparative weight analysis is conducted between the baseline and retrofitted aircraft. The study concludes with a critical examination of the benefits and challenges related to the All Electric Aircraft concept.